Strategies to optimize methane production from non-conventional waste - Alves, M. M. (2013)
The greatest technological challenge for human society today is the replacement of fossil fuels by energy sources that are renewable and carbon neutral. The most likely way that this challenge will be met is by using microorganisms, which have the potential to generate large flows of renew able energy. Wastewaters, sludges, residues, and other 'wastes of today' must be viewed as resources, within the context "waste-to-energy". Converting the energy value in these wastes to useful energy provides two simultaneous benefits: the gene rat ion of renewable energy and the minimization of environmental pollution. Anaerobic technology has been traditionally applied for the treatment of carbon rich wastewater and organic residues. One of the main advantages of anaerobic digestion is the possibility of recovering renewable energy in the form of biogas, which is a versatile energy carrier that can be used for electricity production, heating purposes, vehicle and jet fuel and replacement of natural gas by injection of upgraded biogas in the natural gas grid. In addition, biogas may be considered as starting compo und for biotechnological production of chemicals. (…)